Ecofeminist Homoeroticism in two Costa Rican Lesbian Poems (2022)
In this article are analyzed, hermeneutically and correlatively, the poems “Yo y ella” (1987), by Nidia Barboza, and “Tropical” (2018), by Daniela Esquivel. The representation and construction of lesbian lovers is studied, linking the expressions of their homoeroticism with ecofeminism and queer ecology. In Barboza’s poem, the (self)affirmation of lesbianhood linked to the beach and earth elements is observed. In Esquivel’s, the belonging of lesbian bodies to the beach and the naturalization of exhibitionism are also studied. It is concluded that the lyrical actants show, from the paradigm of open LGBTIQ+ eroticism, an ecological awareness and queer empathy, because they integrate nature into their bodies, they live their interdependence and indistinction with nature, they celebrate cosmic belonging and unity; they inhabit, remember and queer the marine ecosystem, where they naturalize and affirm their homosexuality, enjoy and freely and holistically exhibit their homoeroticism, and deconstruct the discourses of the heteronormative, homophobic and ecophobic dwelling.